2017
DOI: 10.1002/advs.201700204
|View full text |Cite
|
Sign up to set email alerts
|

Mixed‐Organic‐Cation Tin Iodide for Lead‐Free Perovskite Solar Cells with an Efficiency of 8.12%

Abstract: In this work, a fully tin‐based, mixed‐organic‐cation perovskite absorber (FA)x(MA)1− xSnI3 (FA = NH2CH = NH2 +, MA = CH3NH3 +) for lead‐free perovskite solar cells (PSCs) with inverted structure is presented. By optimizing the ratio of FA and MA cations, a maximum power conversion efficiency of 8.12% is achieved for the (FA)0.75(MA)0.25SnI3‐based device along with a high open‐circuit voltage of 0.61 V, which originates from improved perovskite film morphology and inhibits recombination process in the device. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
430
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(467 citation statements)
references
References 34 publications
(27 reference statements)
22
430
0
15
Order By: Relevance
“…1) and other absorber materials [710 1213 1620]. Experimental solar cell performance compared to the Shockley–Queisser SQ limit (a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) and other absorber materials [710 1213 1620]. Experimental solar cell performance compared to the Shockley–Queisser SQ limit (a).…”
Section: Discussionmentioning
confidence: 99%
“…The record efficiency of 7.5% [6] is comparable to that of other less investigated materials, such as the best lead-free perovskites [7], Cu 2 O [8] and Sb 2 Se 3 [910] and outperforms bismuth-halides [1112], SnS [13] and Bi 2 S 3 [1416]. However, the efficiency of Sb 2 S 3 trails behind the more thoroughly studied material systems such as lead-based perovskites [17], organic solar cells [1819] or PbS [20], thus further technological investigation is needed.…”
Section: Introductionmentioning
confidence: 96%
“…Lee et al reported FASnI 3 perovskite solar cells in regular mesoporous TiO 2 structure with the addition of pyrazine to achieve a PCE of 4.8%. [70] The PCE of Sn perovskite solar cells is mainly limited by the instability of the absorber materials due to the easy oxidation of Sn 2+ to Sn 4+ . [68] Zhu et al realized FASnI 3 solar cells with a PCE of 7% via a sequential deposition method.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[20,21] Just before the submission of this manuscript, Zhao et al reported tinbased HPSCs with a PCE of 8.12% by using mixed cation tin perovskite (FA 0.75 MA 0.25 SnI 3 ) as light harvesting layer. [22] Despite the relatively high efficiency, the resistance to moisture of FA 0.75 MA 0.25 SnI 3 -based HPSCs should be quite limited because of the hydrophilic FA + and MA + cations.…”
Section: Doi: 101002/aenm201702019mentioning
confidence: 99%